2020
DOI: 10.1088/1757-899x/847/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Using the Bees Algorithm to solve combinatorial optimisation problems for TSPLIB

Abstract: The Bees Algorithm (BA) is a metaheuristic algorithm to find good solutions to optimisation problems in reasonable computing times. This paper is the first to report on the use of the BA to solve 9 combinatorial optimisation problems (COP) with more than 100 cities from TSPLIB rigorously to test the performance of the algorithm. The work employed a basic version of the BA for COP and TSPLIB datasets involving between 100 and 200 cities. The results obtained show that deviations from the best-found tour lengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
0
30
0
1
Order By: Relevance
“…In general, the positions of the members in the problem are changed according to certain rules, and new sequences are tried to be found with less cost. For the Bees Algorithm, Ismail et al [26] suggested three different operators in the local search section, namely, Swap, Insertion, and Inversion.…”
Section: The Online Bees Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the positions of the members in the problem are changed according to certain rules, and new sequences are tried to be found with less cost. For the Bees Algorithm, Ismail et al [26] suggested three different operators in the local search section, namely, Swap, Insertion, and Inversion.…”
Section: The Online Bees Algorithmmentioning
confidence: 99%
“…In the swap process, the order of two different vehicle groups chosen at random is changed with each other [26]. As an example in Fig.…”
Section: The Online Bees Algorithmmentioning
confidence: 99%
“…The basic BA, which was initially developed in 2005 to solve continuous problems, [ 5 ] has been improved to its combinatorial versions on solving PCB assembly, timetabling, machine scheduling, and TSP. [ 11,12 ] Combinatorial and continuous versions of BA principally have a similar general procedure. The only difference between the two versions is in the local search phase of the algorithm.…”
Section: The Combinatorial Bees Algorithm and Its Implementation To Tmentioning
confidence: 99%
“…The relationships’ assumption of parameter setting was taken from Pham et al. [ 11 ] that was also used by the previous study by Ismail et al. [ 12 ]…”
Section: The Combinatorial Bees Algorithm and Its Implementation To Tmentioning
confidence: 99%
“…Existing populationbased optimisation algorithms need to operate with large populations and, as a result, are generally slow. The Bees Algorithm [14] is a population-based algorithm that has been successfully employed to solve many complex real-world optimisation problems including continuous [15] and combinatorial [16] optimisation problems. It is able to find both local and global optima without needing to calculate the gradient of the objective function.…”
Section: Introductionmentioning
confidence: 99%